Murales et rayados de Valparaíso : entre institutionnalisation et vandalisme - Elsa Bouvier (Les Cahiers de Framespa)
The harbour Valparaíso city shelters an intense graffiti’s activity : it became a major nerve center of the Chilean graffiti. The diversity of the urban inscriptions sends back to different relationships with the authority, and the wall / rayado cleavage crystallizes the political and media debate around the porteñas’ urban inscriptions. The radical opposition between mural and rayado, widely built by the political speech of the municipality, results from criteria of acceptance of the urban inscriptions on behalf of this institution, but also of its conception of the public place and its patrimonial and cultural urban public politics. In front of social control exercised by the municipality and its institutions, the practices and the postures of the graffiti artists join a tension between legality and illegality, between vandalism, contesting and institutionalization, artification, patrimonialisation.